Exploring relationships between time of day and pollinator activity in the context of pesticide use - Arrian Karbassioon; Dara A. Stanley (Basic and Applied Ecology, 2023)
Pesticide exposure can be harmful to insect pollinators and the ecosystem services they provide. As many pesticide guidelines warn against applying such products when pollinators are active, it is important to evaluate how pollinator activity changes with time of day to determine the most appropriate time to spray.We walked transects from sunrise to sunset in oilseed rape (Brassica napus L.) fields in Ireland to capture the abundance of honeybees, bumblebees, solitary bees, and hoverflies across daylight hours. We also recorded the activity of representative species from the three bee groups at their nests across similar time periods to compare with field observations.Peak pollinator abundance was in the mid-afternoon with fewer individuals in the early morning and late evening for all groups. At the nest we observed patterns of activity that broadly reflected field abundance but indicated that bees are active earlier and later than observed on the crop. However, there were differences between pollinator groups. Overall, honeybee and solitary bee abundance and activity were found to peak in the middle of the day, while bumblebee abundance and activity was more consistent throughout daylight hours. Hoverflies were relatively abundant in the morning and increased in number towards the late afternoon and early evening.Our results confirm current recommendations that pesticide application should be avoided in the middle of the day when pollinators are most active. However, the diversity of responses within and between pollinator groups to time of day should be accounted for when shaping guidelines, and clearly defining optimal pesticide application timings for end users is difficult and needs further consideration as it will vary between regions and crops. Further research should also explore how time impacts both pesticide efficacy and exposure of pollinators to residues post-application to allow full evaluation of how practical and beneficial timing of application may be when aiming to protect pollinators from pesticide exposure.